2015
DOI: 10.1007/s00705-015-2538-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of zoonotic viruses in swine fecal samples in Italian pig herds

Abstract: Gastrointestinal disease is frequent in pigs, and among the different etiological agents involved, viruses are considered the leading cause of infection in this animal species. Furthermore, about half of the newly identified swine pathogens are viruses, many of which may be transmitted to humans by direct contact or by indirect transmission pathways. In this study, the prevalence of astrovirus (AstV), group A rotavirus (RVA), norovirus (NoV) and hepatitis E virus (HEV) infections in pigs was investigated. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
2
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 49 publications
(56 reference statements)
7
44
2
4
Order By: Relevance
“…Molecular tracking of enteric viral markers in the network began by investigating farm sites where their natural hosts reside. RVAs and PoAstVs were detected in swine feces from all farms and revealed extensive genetic diversity of strains consistent with previous publications from Canada and elsewhere (8,9,(36)(37)(38)(39). However, to our knowledge, detection and characterization of viral strains derived from environmental samples has not been thoroughly investigated to date.…”
Section: Discussionsupporting
confidence: 86%
“…Molecular tracking of enteric viral markers in the network began by investigating farm sites where their natural hosts reside. RVAs and PoAstVs were detected in swine feces from all farms and revealed extensive genetic diversity of strains consistent with previous publications from Canada and elsewhere (8,9,(36)(37)(38)(39). However, to our knowledge, detection and characterization of viral strains derived from environmental samples has not been thoroughly investigated to date.…”
Section: Discussionsupporting
confidence: 86%
“…These studies showed that the prevalence of HEV RNA in swine faeces and serum depend on the production stage, i.e. the pig’s age (Additional file 2 [14, 15, 18, 21, 57, 66, 86–89, 91–93, 95, 96, 104, 108, 109, 113, 114, 118–120, 133, 135, 136, 140–150]). A broad shedding period from 1.5 to 5 months of age was globally reported at farm scale.…”
Section: Hev Infection Characteristics and Dynamics On Pig Farmsmentioning
confidence: 99%
“…It is widely accepted that breeding sows can play a role as HEV reservoirs and can transmit the virus to sucking piglets [144, 148, 156, 159, 160]. Pigs of less than 2 months are protected against HEV infection due to the presence of maternal antibodies [140, 161, 162]. HEV infection in pigs is subclinical, with only microscopic liver lesions [140, 163].…”
Section: Hev In Animalsmentioning
confidence: 99%
“…Although infection in pigs seems to occur at early stages in animal life, virus can be detected at all ages [156, 160, 162, 164]. On the other hand, RNA has been found in feces, liver, bile, and cecal content of animals at slaughter age, representing a risk of entrance of HEV into the food chain [149, 150, 157, 160].…”
Section: Hev In Animalsmentioning
confidence: 99%